1996
DOI: 10.1099/00207713-46-4-981
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Thiosulfate by a New Bacterium, Bosea thiooxidans. (strain BI-42) gen. nov., sp. nov.: Analysis of Phylogeny Based on Chemotaxonomy and 16S Ribosomal DNA Sequencing

Abstract: A gram-negative bacterium which was capable of oxidizing reduced inorganic sulfur compounds was isolated from agricultural soil and designated BI-42. This new isolate grew on a wide range of organic substrates but was not able to grow autotrophically and lacked ribulose 1,s-bisphosphate carboxylase, a key enzyme of carbon dioxide fixation. These results suggested that strain BI-42 was a chemolithoheterotroph. Ammonia and nitrate were not used as sole nitrogen sources for growth, and strain BI-42 lacked glutama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
70
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 25 publications
(4 reference statements)
2
70
0
2
Order By: Relevance
“…The 16S rRNA gene of strain S10 T was amplified as described previously (Das et al, 1996;Patra et al, 2007). The 16S rRNA gene sequence (1440 nt) thus obtained was compared with those in GenBank and the Ribosomal Database Project (Maidak et al, 1997) after BLAST searches (Altschul et al, 1997).…”
mentioning
confidence: 99%
“…The 16S rRNA gene of strain S10 T was amplified as described previously (Das et al, 1996;Patra et al, 2007). The 16S rRNA gene sequence (1440 nt) thus obtained was compared with those in GenBank and the Ribosomal Database Project (Maidak et al, 1997) after BLAST searches (Altschul et al, 1997).…”
mentioning
confidence: 99%
“…Phylogenetic characterization found that this bacterium is grouped with the class alpha-Proteobacteria, specifically with Bosea thiooxidans, within 99% of shared identity. Bosea thiooxidans is a reported heterotrophic, strict aerobe, and inorganic sulfur oxidizer [118]. After isolating, mineral studies with arsenopyrite and pyrite-bound As confirmed that Bosea WAO oxidizes sulfide and arsenite [119].…”
Section: Enargite Bioleaching With Neutrophilic Microorganismsmentioning
confidence: 99%
“…The genus currently encompasses a single species with a validly published name, Microvirga subterranea, and is assigned to the class Alphaproteobacteria, phylum Proteobacteria (Garrity & Holt, 2001;Garrity et al, 2005a), almost equidistant from Methylobacterium species (Patt et al, 1976;Urakami et al, 1993) Egli et al, 1988) and Bosea thiooxidans (Das et al, 1996), its nearest phylogenetic relatives, with a mean similarity value of 93 %.…”
mentioning
confidence: 99%
“…Phase-contrast and electron microscopy of cells were performed as described by Andrews & Patel (1996). The presence of flagella and spores was assessed by the method of Das et al (1996) and Kanso & Patel (2003). The GenBank/EMBL/DDBJ accession number for the 16S rRNA gene sequence of strain 25B T is EU727176.…”
mentioning
confidence: 99%
See 1 more Smart Citation